2009
DOI: 10.1007/s10535-009-0119-7
|View full text |Cite
|
Sign up to set email alerts
|

QTLs mapping of physiological traits related to salt tolerance in young rice seedlings

Abstract: Oryza sativa L. F 2 population and F 2:3 derived from a cross between salt tolerance cv. Tarommahali and salt sensitive cv. Khazar were used in this study. A linkage map based on F 2 population was constructed (74 SSR markers on 192 individuals), which covered a total of 1231.50 cM with an average two locus interval of 19.83 cM. Two QTLs related to Na + /K + ratio were found on chromosome 3 and 6. qDM-3 and qDM-8 (for dry mass of shoot) are major QTLs with very large effects explained 20.90 and 17.72 % of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 27 publications
2
39
0
Order By: Relevance
“…Therefore, screening for salt tolerance at reproductive stages has been considered to be more useful. The use of physiological characters as selection criteria in salt tolerance breeding requires the identification of the contribution of each individual character to salt tolerance (Sabouri et al, 2009). Panicle weight, tiller numbers per plant and harvest index are important agronomic characters for the prediction of rice yield.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, screening for salt tolerance at reproductive stages has been considered to be more useful. The use of physiological characters as selection criteria in salt tolerance breeding requires the identification of the contribution of each individual character to salt tolerance (Sabouri et al, 2009). Panicle weight, tiller numbers per plant and harvest index are important agronomic characters for the prediction of rice yield.…”
Section: Introductionmentioning
confidence: 99%
“…Saltol belongs to QTL and has been defined in chromosome 1 of salt tolerant Pokkali rice [25,26]. A technology of molecular genetic screening for salt tolerance enables to immediately select forms of plants having target genes and create varieties with predefined properties and without using challenges [27,28]. According to literature data, introduction of Saltol QTL into highly productive varieties stabilizes the rice yields in saline soils [29].…”
Section: Screening Of Rice (Oryzamentioning
confidence: 99%
“…To screen for polymorphisic loci, 12 genotypes (Laotoudao 1, Baidadu, Kendao 12, Xiaobaijingzihuadianbai, Jijing 61, Danjing 8, Shennong 91, Fushiguang, Kongyu 131, Yuntoudao, Zaojinfu, and Pingrang 10), three from Heilongjiang, two each from Jilin, Liaoning, Japan, and Korea, one from DPRK, were selected for primer amplification. Finally, 160 SSR markers were selected to genotype the panel of japonica rice, including 25 markers known to be linked to salt-tolerant QTLs from previous studies (Ammar et al 2009;Mohammadi-Nejad et al 2008;Sabouri et al 2009;Thomson et al 2010;Wang et al 2012a, b).…”
Section: Ssr Marker Genotypingmentioning
confidence: 99%
“…ratio (SKN) is also an important indicator to evaluate salt tolerance in rice. In recent decades, using the rice seedling salt tolerance indicators mentioned above and other indicators, many studies have been reported with linkage mapping of QTL for salt tolerance at the seedling stage (Kim et al 2009;Bonilla et al 2002;Koyama et al 2001;Lee et al 2007;Lin et al 2004;Prasad et al 2000;Sabouri et al 2009;Zang et al 2008). For example, 11 QTLs for survival days of seedlings and the Na ?…”
Section: Introductionmentioning
confidence: 99%